The Views of Saadia Gaon and al-Qāḍī Abd al-Jabbār on God's Justice and Their Relevance to Dialogue among Civilizations - Hasan, Pipip A. Rifai; Sunaryo, Sunaryo (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The surge in scholarly fervor across the Arab world following the Hellenistic resurgence instigated shifts in religious thought concerning theodicy. Saadia Gaon and al-Qāḍī Abd al-Jabbār, representing Jewish and Islamic scholars respectively, exemplify this evolving trend. This study endeavors to delve into Gaon and al-Qāḍī Abd al-Jabbār's perspectives on divine justice and its implications for human agency. Employing a qualitative approach with content analysis as the analytical tool, this research reveals a convergence of ideas between Gaon and al-Qāḍī regarding the manifestation of divine justice through human autonomy. This autonomy operates within the framework of revealed restrictions transmitted to the messenger of God. These limitations establish a moral framework delineating choices of good and evil, ultimately entrusted to human discretion guided by reason. The primacy of reason underscores moral rationality, guiding individuals towards virtuous conduct. Within the realm of human freedom, diverse actions unfold, contributing to cultural evolution and the advancement of civilization. Moral rationality emerges as a pivotal tool in religious comprehension, fostering dialogue between Abrahamic faiths and facilitating the pursuit of a more cohesive global society.